Nilai-nilai Pendidikan Akhlak dalam Kitab Taisīril Khallāq dan Relevansinya dengan Pendidikan Islam di Era Digital - Khanifah, Putri (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The book of Taisīril Khallāq is one of the books containing a summary of basic moral knowledge authored by Shaykh Hafidz Hasan Al-Mas'udi. The purpose of this study is to examine the values of moral education contained in the book of Taisīril Khallāq and analyze its relevance to Islamic education in the digital era. This research combines library research methods with a qualitative approach. By using content analysis as a method of data analysis, the analysis is carried out by examining carefully, namely by reading and evaluating the contents of the book of Taisīril Khallāq. Referring to the results obtained from the data analysis, the book of Taisīril Khallāq contains moral education values such as devotion to Allah SWT, morals to fellow human beings, including the obligations and rights of parents, family, and neighbors, manners in association, harmony, brotherhood, and meetings, as well as morals to oneself, including cleanliness, honesty, reliability, al-‘iffah, al-muru'ah, patience, generosity, tawadlu’, height of soul, and justice. These values include universal values so that they are relevant to Islamic education in the digital era because they can help students develop morals, develop personality, develop critical thinking skills, and develop effective communication skills. Therefore, moral education in the book of Taisīril Khallāq can be integrated in the Islamic education curriculum in the digital era.